FUTURE OF CONSTRUCTION INDUSTRIES IN INDIA - MR. MAYUR LALITKUMAR LODHA; MRS. ASHA OAK (International Journal of Innovations in Engineering Research and Technology, 2021)
Indian government is motivating the construction industry by means of the urban transformation. The schemes like Smart cities development leads to the great support to the construction industry by means of the major projects.On the other hand the projects like the metro rails and bullet trains have great opportunitiesfor construction industries to contribute. The government is also dreaming for housing to all by means of PradanMantri Awas Yojana in India, where the challenge is to provide the subsidy on houses to all the middle class Indians. In coming decade the construction industries have great opportunities in India to develop there by transforming thepresent technology to next level in view of the sustainable development ofIndia. Authors have presented the overview of future of the construction Industries in India in this paper.